Influence of microporous gelatin hydrogels on chondrocyte functions. Issue 29 (7th July 2017) - Li, Xiaomeng; Chen, Ying; Kawazoe, Naoki; Chen, Guoping
Abstract : Gelatin hydrogels with microporous structures were prepared by polymerization of GelMAGMA macromers and dissolution of gelatin hydrogel microcubes. The microporous gelatin hydrogels promoted proliferation of chondrocytes and showed different cellular effects compared to hydrogels without microporous structures. Abstract : Hydrogels can provide biomimetic three-dimensional microenvironments for transplanted cells and are attractive scaffolds for cartilage tissue engineering. In this study, gelatin hydrogels with microporous structures were prepared and their effects on chondrocyte functions were compared with gelatin hydrogels without microporous structures. Gelatin bulk hydrogels were prepared by photo-initiated crosslinking of gelatin methacrylate macromers. Micropores were formed in the bulk hydrogels by dissolution of gelatin microgels prepared by a cutting method. Chondrocytes cultured in gelatin hydrogels without microporous structures showed high expression and production of cartilaginous matrices and low cell proliferation. Chondrocytes cultured in gelatin hydrogels with microporous structures tended to migrate from bulk hydrogel matrices to the micropores. Chondrocytes in the microporous hydrogels showed higher proliferation and lower expression and production of cartilaginous matrices than did the chondrocytes cultured in hydrogels without microporous structures. Gelatin hydrogels without microporous structures facilitated maintenance of the cartilaginous phenotype of the chondrocytes while microporous gelatin hydrogels were beneficial for cell proliferation.